2016
DOI: 10.4049/jimmunol.1502445
|View full text |Cite
|
Sign up to set email alerts
|

Essential Requirement for IFN Regulatory Factor 7 in Autoantibody Production but Not Development of Nephritis in Murine Lupus

Abstract: Systemic lupus erythematosus (SLE) is a prototypic systemic autoimmune disease characterized by the production of autoantibodies against nuclear components. Recent genetic studies of SLE patients have revealed that IFN regulatory factor (IRF) 7 gene polymorphisms are associated with an increased risk of SLE, but the precise role of IRF7 in SLE development is not fully understood. We investigated the role of IRF7 in the pathogenesis of SLE using a mouse model and saw a curious dissociation of autoantibody produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
4
14
0
Order By: Relevance
“…[30][31][32][33] Moreover, evidence showed that genetic variants of IRF7 were associated with diverse anti-double-stranded (ds)DNA production in SLE. 34 Miyagawa et al 35 reported that serum INF-α levels were reduced in an SLE mice model with IRF7 knockout compared to the wild type, and also found that those mice were unable to produce multiple kinds of autoantibodies, which further implied the strong linkage between IRF7 and antibody formation. using a luciferase reporter assay, they proved that the risk allele of rs1131665 could lead to a twofold increase in transcriptional activity of an IFN-stimulated response element compared to that of the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] Moreover, evidence showed that genetic variants of IRF7 were associated with diverse anti-double-stranded (ds)DNA production in SLE. 34 Miyagawa et al 35 reported that serum INF-α levels were reduced in an SLE mice model with IRF7 knockout compared to the wild type, and also found that those mice were unable to produce multiple kinds of autoantibodies, which further implied the strong linkage between IRF7 and antibody formation. using a luciferase reporter assay, they proved that the risk allele of rs1131665 could lead to a twofold increase in transcriptional activity of an IFN-stimulated response element compared to that of the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that NF-κB pathway-dependent glomerulonephritis still occurred in Irf7 −/− mice after administration of TMPD [ 9 ]. In this study, we determined the contribution of IRF8 to the development of glomerulonephritis because IRF8 controls NF-κB pathway in addition to type I IFN pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Freshly isolated peritoneal cells from WT, Irf7 −/− , or Irf8 −/− mice were grown in complete RPMI in the presence or absence of TMPD. Due to its insolubility in aqueous medium, TMPD was added as the inclusion complexes with β-cyclodextrin (β-CyD; Wako) as described previously [ 9 ]. In some experiments, single cell suspensions were prepared from inguinal lymph nodes (LNs) and spleen from three strains and cultured with or without TMPD as described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations